An Islamic Criminal Law Perspective on the Misuse of Subsidized Fuel: Case Study of Decision No. 116/PID.B/LH/PN PSB - Hamdani; Illahi, Kurnia Fitri (JLAST : Journal of Law and Social Transformation, 2025)
This study examines the legal considerations used by the Panel of Judges in imposing criminal sanctions on the defendant in Decision No. 116/Pid.B/LH/2023/PN Psb regarding the criminal act of misuse of government-subsidized fuel trading. Although Article 55 of Law Number 22 of 2001 on Oil and Gas stipulates a maximum penalty of six years in prison and a fine of up to Rp60,000,000,000.00, the defendant was only sentenced to six months in prison and fined Rp50,000,000.00. This study aims to analyze the judge's rationale for imposing the sanction and to examine the verdict from the perspective of Islamic criminal law. This research employs a qualitative approach using a case study method. Primary data was obtained through direct interviews with judges at the West Pasaman District Court, while secondary data was collected from books, journals, legislation, and Islamic legal sources such as the Qur’an and Hadith. The findings indicate that the judge's considerations in sentencing were based on the elements of the criminal act under Article 55 of Law No. 22 of 2001 jo. Article 55, paragraph (1) of the Criminal Code, available evidence, and aggravating and mitigating factors. Additionally, the judge considered consistency with previous decisions that have permanent legal force to prevent sentencing disparities in similar cases. From the perspective of Islamic criminal law, the defendant’s actions fall under jarimah ta'zir as they constitute an unlawful act that does not fall within hudud or qisas. While the act could be linked to the concept of al-baghyu (rebellion), the absence of violence or weapon use classifies the punishment under ta'zir, allowing the judge discretion in determining the appropriate sanction.